'They make a business out of desperate people': The role of recruitment agents in cross-border labour chains. Issue 4 (November 2021) - Stringer, Christina; Kartikasari, Ani; Michailova, Snejina
This article examines the role recruitment agents play in the complex web of forced labour. Our focus is the abusive treatment of Indonesian crew onboard South Korean factory trawlers fishing in New Zealand's waters. We gathered data from multiple sources: (1) documents, including Indonesia's national legislation and migrants' employment contracts; (2) 27 interviews with Indonesian crew; and (3) translation work for New Zealand government ministries, court cases, and film productions. We analyse how recruitment agents are implicated, as seen through the crew's eyes, in three phases – before departure, onboard the vessels, and following their return home. JEL Classification:J81, F55, F66